Production of Methanol from Aqueous CO2 by Using Co3O4 Nanostructures as Photocatalysts. (9th January 2019) - Pocoví-Martínez, Salvador; Zumeta-Dube, Inti; Diaz, David
Abstract : In this work, we report for the first time the photocatalytic activity of Co3 O4 nanostructures for the reduction of aqueous CO2 to methanol (MeOH). This could be considered a simple example of artificial photosynthesis. The photocatalysis experiments were developed under simulated solar light of 100 mW/cm 2 and without using any sacrificial agent. To carry out this study, nanostructured mixed valence cobalt oxide (Co3 O4 ) powders, with porous nanoparticle aggregates of different morphologies, have been prepared by two synthesis methods. The characterization of structural (PXRD, XPS, SEM, and TEM) and optical (UV-vis-NIR, Raman, and FT-IR) properties, magnetization curves, and surface area (BET) was accomplished.